The Reality Of The Level Of Community Participation In Assisting Law Enforcement In Areas Controlled By Terrorist Groups - Fahmi Sidiq (Jurnal Scientia, 2024)
There are many challenges to efforts to eradicate terrorism in Indonesia. In 2021, in Central Sulawesi Province, an operation took place against a terrorist group called the East Indonesian Mujahidin (MIT) through a tough approach carried out by the Indonesian Counter-Terrorism Task Force. It took years to resolve and apparently, there were other important issues. This means that people are afraid to provide important information about the terrorist group to law enforcement officials. This particular situation made it difficult for the CT task force to work. All of the above will be examined from a Criminology perspective on how community participation can influence counter-terrorism. This research will use a qualitative approach by conducting interviews with officers and members of the public who have met directly with terrorist groups in Central Sulawesi. The impact is quite clear that fear of terrorism can influence community participation.